Low health literacy is associated with patient–clinician discrepancy in the perceived severity of medical emergencies - Nuernberger, Matthias; Lehmann, Thomas; Brodoehl, Stefan; Huebner, Jutta; Lewejohann, Jan-Christoph (Frontiers in Public Health, 2025)
IntroductionMost adults in the United States and Europe have low health literacy (HL), which also has an impact on emergency care. It is unclear, whether low HL impairs the patients’ ability to evaluate the seriousness of their emergency and if it increases patient-clinician disagreement.MethodsIn this prospective cross-sectional study in a German tertiary-care emergency department (ED), 257 adults (median age = 55 y) self-assessed the severity of their condition on arrival; simultaneously, an ED nurse and physician provided independent assessments. Thirty days later, an expert panel reviewed each case and issued a specialist evaluation. HL was assessed with the 16-item European Health Literacy Survey (HLS-EU-Q16) and categorized as adequate (n = 95), problematic (n = 119), or inadequate (n = 43). Three discrepancy indices were computed from age-, gender-, and education-adjusted assessments. Spearman correlations and Kruskal–Wallis tests compared agreement across HL levels; linear and logistic regressions examined predictors of discrepancy and severe outcome.ResultsPatients with adequate HL showed the strongest alignment with clinicians (ρ = 0.24), whereas correlations were weaker in the inadequate group (ρ = 0.18). Discrepancies decreased as HL improved (β = −0.12 to −0.19, p < 0.05), but HL alone explained only up to 7% of variance. Concordant assessments increased with rising HL. Overestimation was most prevalent at inadequate HL level. In multivariable logistic modeling, each one-point increase in the Patient to Medical Team discrepancy raised the odds of a severe outcome by 27% (OR = 1.27, 95% CI [1.04, 1.55]), whereas each additional HL score point lowered the odds by 13% (OR = 0.87, 95% CI [0.77, 0.99]).ConclusionLower HL modestly but consistently enlarges the gap between patients’ and clinicians’ emergency assessments and is associated to a higher likelihood of a severe outcome via this mismatch. Although adequate HL improves agreement, half of these patients still struggle to evaluate severity. Routine teach-back communication might be helpful to identify discrepancies. These findings underscore the need for healthcare professionals to assess patients without prejudice, regardless of presenting symptoms, to ensure optimal medical care.Trial registrationIdentifier, DRKS00032962.